Pengukuran Kinerja Customer Relationship Management (CRM) CDMA Esia Menggunakan CRM Scorecard Pada PT Bakrie Telecom Tbk - Didien Suhardini; Suci Lestari (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
Bakrie Telecom realizes it is importance to know the customer needs that have not been fulfilled and the effectiveness of its CRM (Solusi Esia). The purpose of this study is to analyze the Importance-Performance Matrix and designing performance measurement systems and measure of Solusi Esia performance, then propose development program of Solusi Esia for the next year. Designing a CRM Scorecard start from cascading the vision, mission and strategy of the company to the vision, mission and strategy of Solusi Esia, then translate into fours CRM Scorecard perspective, setting strategic objectives, building a strategy map, set targets, and strategic initiatives and weighing of each strategic objective as lag indicators relative to a leading indicator in each perspective using pair wise comparisons. The score of Solusi Esia Performance is 3.46 considered good. Some development programs are call center phone charge change to be free of charge, establish training centers, network operations, voice recording the conversation between costumer and costumer service and periodically doing a market survey.